PENGARUH INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN DI PROVINSI KALIMANTAN BARAT TAHUN 1992 - 2011 - B61111037, ERIANSYAH (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This study was done to analyze the impact of inflation and economic growth on the unemployment rate in West Kalimantan period 1992-2011. The data were analyzed by using Multiple Linear Regression. The hypotheses were tested using partial T-test, partial F-test, and coefficients of determination test (R2). This study found that the inflation trend is insignificantly influential to the unemployment rate it was shown by the result of significant level 0,273 > 0,05. On the other side, the unemployment rate and economic growth show negative significant influent at 0,038 < 0,05significant level with -0,282 regression. Meanwhile, test of inflation variable and economic growth variable show significant influent to the unemployment rate at 0,000 < 0,05significant level. These result indicate that inflation and economic growth are simultaneously influent to the unemployment. Key words: Inflation, Economic Growth, Unemployment